A Human Immunodeficiency Virus Type 1 Tat-Like Arginine-Rich RNA-Binding Domain Is Essential for HEXIM1 To Inhibit RNA Polymerase II Transcription through 7SK snRNA-Mediated Inactivation of P-TEFb - Yik, Jasper H. N. (American Society for Microbiology, 2004)
The HEXIM1 protein inhibits the kinase activity of P-TEFb (CDK9/cyclin T) to suppress RNA polymerase II transcriptional elongation in a process that specifically requires the 7SK snRNA, which mediates the interaction of HEXIM1 with P-TEFb. In an attempt to define the sequence requirements for HEXIM1 to interact with 7SK and inactivate P-TEFb, we have identified the first 18 amino acids within the previously described nuclear localization signal (NLS) of HEXIM1 as both necessary and sufficient for binding to 7SK in vivo and in vitro. This 7SK-binding motif was essential for HEXIM1's inhibitory action, as the HEXIM1 mutants with this motif replaced with a foreign NLS failed to interact with 7SK and P-TEFb and hence were unable to inactivate P-TEFb. The 7SK-binding motif alone, however, was not sufficient to inhibit P-TEFb. A region C-terminal to this motif was also required for HEXIM1 to associate with P-TEFb and suppress P-TEFb's kinase and transcriptional activities. The 7SK-binding motif in HEXIM1 contains clusters of positively charged residues reminiscent of the arginine-rich RNA-binding motif found in a wide variety of proteins. Part of it is highly homologous to the TAR RNA-binding motif in the human immunodeficiency virus type 1 (HIV-1) Tat protein, which was able to restore the 7SK-binding ability of a HEXIM1 NLS substitution mutant. We propose that a similar RNA-protein recognition mechanism may exist to regulate the formation of both the Tat-TAR-P-TEFb and the HEXIM1-7SK-P-TEFb ternary complexes, which may help convert the inactive HEXIM1/7SK-bound P-TEFb into an active one for Tat-activated and TAR-dependent HIV-1 transcription.